Begonia tadungensis (Begonia sect. Platycentrum), a new species from southern Vietnam - Do, Truong Van; Luu, Anh Ngoc Dam; Dong, Wen-Ke (Phytotaxa, 2020)
We here describe and illustrate Begonia tadungensis (B. sect. Platycentrum), a new species from southern Vietnam. The new species is most similar to B. albopunctata in having broadly ovate leaves, three free styles, 4-loculed ovary, and berry-like fruits with a beaked apex, but differs mainly in having a glabrous abaxial leaf surface (not densely red pubescent), and fruits with gray puberlous hairs (not white papillose). It is also similar to B. pendens in its broadly ovate leaves and monoecious breeding system, but differs in having 6 tepals in the pistillate flowers (not 5) and 4-loculed ovaries (not 3-loculed). Information on ecology, conservation status, and a further comparison of characters with these two similar species is also provided.